2016
DOI: 10.1242/jcs.182592
|View full text |Cite
|
Sign up to set email alerts
|

Innervation regulates synaptic ribbons in lateral line mechanosensory hair cells

Abstract: Failure to form proper synapses in mechanosensory hair cells, the sensory cells responsible for hearing and balance, leads to deafness and balance disorders. Ribbons are electron-dense structures that tether synaptic vesicles to the presynaptic zone of mechanosensory hair cells where they are juxtaposed with the post-synaptic endings of afferent fibers. They are initially formed throughout the cytoplasm, and, as cells mature, ribbons translocate to the basolateral membrane of hair cells to form functional syna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…2G), supporting that ngn1 morphant zebrafish hair cells are morphologically and, at least in part, functionally mature despite lacking afferent and efferent innervation. It should be noted that hair-cell innervation is important for synaptic-ribbon maintenance in zebrafish36 and afferent innervation plays a significant and variable role in long-term hair-cell maintenance and viability in mice37. Nevertheless, previous studies have shown that short term hair-cell survival is possible in the absence of innervation38, indicating ngn1 morphants as a useful tool in determining whether iGluR agonist exposure damages hair cells in the absence of innervation.…”
Section: Resultsmentioning
confidence: 99%
“…2G), supporting that ngn1 morphant zebrafish hair cells are morphologically and, at least in part, functionally mature despite lacking afferent and efferent innervation. It should be noted that hair-cell innervation is important for synaptic-ribbon maintenance in zebrafish36 and afferent innervation plays a significant and variable role in long-term hair-cell maintenance and viability in mice37. Nevertheless, previous studies have shown that short term hair-cell survival is possible in the absence of innervation38, indicating ngn1 morphants as a useful tool in determining whether iGluR agonist exposure damages hair cells in the absence of innervation.…”
Section: Resultsmentioning
confidence: 99%
“…The first mature and functional HCs can be found in the LL and inner ear as early as 3dpf, even if the maturation process is ongoing in both structures into adulthood [13,85]. HC innervation also happens early and is extensively documented in the LL [86][87][88], and it was demonstrated that innervation regulates ribbon synapses development and maturation [32]. Interestingly, we did not find overt defects in the sensory or motor innervation of NMs, thus suggesting that the defects observed in the sensory synapses were HC autonomous, but this remains to be tested.…”
Section: Cnr2 Dependent Maturation Of Ribbon Synapsesmentioning
confidence: 99%
“…Furthermore, both the size and number of ribbons per sensory cell vary depending on the species [25], the cell type [25], the position in the sensory epithelium [26], the developmental stage [27,28], and the sensory activity [29]. In the LL of zebrafish larva, mature HCs arise as early as 3dpf, in which three to four spherical ribbons (diameter ~200-300nm) neatly arranged in the basolateral portion can be visualized [24,[30][31][32]. Tethered spherical (diameter ~20-30nm) glutamate-filled vesicles surround the ribbon body.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to electron micrographs, quantitative analysis of immunolabeled epithelial whole mounts provide the advantage of being able to examine synaptic features of large numbers of hair cells. This advantage has been used by a number of groups to characterize relative variances in size and morphologies of pre- and postsynaptic components in mammalian and zebrafish hair-cell organs ( Wong et al, 2014 ; Paquette et al, 2016 ; Suli et al, 2016 ; Becker et al, 2018 ; Jean et al, 2018 ). Further benefits of using the larval zebrafish lateral-line system for quantitative imaging of immunolabeled structures are twofold.…”
Section: Toolkit To Assess Hair-cell Synapse Function and Morphologymentioning
confidence: 99%
“…Further benefits of using the larval zebrafish lateral-line system for quantitative imaging of immunolabeled structures are twofold. First, the relative simplicity; each neuromast contains 10–16 hair cells with ∼3 synapses per cell of similar morphology, making comparative analyses of synapses in numerous lateral-line organs straightforward ( Sheets et al, 2012 ; Suli et al, 2016 ). This in contrast to mammalian auditory hair cells where the number and size of synapses can vary among individual hair cells depending on location within the Organ of Corti—the sensory organ for hearing ( Meyer et al, 2009 ).…”
Section: Toolkit To Assess Hair-cell Synapse Function and Morphologymentioning
confidence: 99%